Improving the physical, emotional and social components of the learning environment: several classroom considerations to enhance adult learning / Jelani Sulaiman - Sulaiman, Jelani (Universiti Teknologi MARA Cawangan Pahang, 1993)
This paper focuses on the three components of the learning environment or climate within the framework of the classroom, namely the physical, emotional or psychological, and social environments which need to be shaped in order to enhance adult learning. It describes some of the instructional considerations necessary to improve the quality of the adult learning climate. Recommendations toward creating a conducive adult learning environment are highlighted.